Correlation Structure of Solar Radio Bursts in Accordance with Solar Activity - Saifuddin Ahmed Jilani; Sana Wajih (Journal of Basic & Applied Sciences, 2018)
Sun is the nearest star that employs us an opportunity to study the behavior of celestial bodies and their influence on Earth’s atmosphere. This paper investigates the dynamics of Solar Radio Bursts (SRB) with respect to their frequencies type II, type III and Mixed type in accord with Sun Spot Number (SSN) over a span of (1996-2010) base over monthly values. Data from National Oceanic and Atmospheric Administration (NOAA) Space Weather Centre were used in this study. This period covers one full and two partial solar cycles. The ionosphere plays a significant role in radio wave communication, therefore the critical frequency of F2 layer (foF2), Maximum electron density (NmF2) Plasma frequency (fP) and Sudden Ionosphere Disturbance (SID) also been included. In various ionospheres quantifications, solar activity such as SSN and 10.7 cm radio flux were used. However SRB influence being considered as a separate variable has not been investigated. The relationship of SRB with Solar Cycle and a comparative study of the influence of these solar variables on ionosphere F2 layer have investigated. The model equations are developed between those variables that have a significant relationship. These equations may be helpful to forecast perturbations in respect of the solar activity.